Framed, Therefore Real - Ecem Ergin (Materia Arquitectura)
With the rise-of the post-truth era, well- known definitions of urban activism have been calling for an update. Covering different territories and media, this essay aims at suggesting new ways of thinking about architecture and its digital representation as a medium for political engagement. It is my suggestion that, the information of space, or more precisely, architecture, can be deployed to reduce the ‘uncertainty’ of a message encountered online and can therefore